Implementation and outcome of thrombolysis with alteplase 3-4·5 h after an acute stroke: an updated analysis from SITS-ISTR - Ahmed, Niaz; Wahlgren, Nils; Grond, Martin; Hennerici, Michael G.; Lees, Kennedy R; Mikulik, Robert; Parsons, Mark; Roine, Risto O; Toni, Danilo; Ringleb, Peter A. (The lancet, 2010)
Background - In September, 2008, the European Acute Stroke Study III (ECASS III) randomised trial and the Safe Implementation of Treatment in Stroke-International Stroke Thrombolysis Registry (SITS-ISTR) observational study reported the efficacy and safety of the extension of the time window for intravenous alteplase treatment from within 3 h to within 4·5 h after stroke onset. We aimed to assess the implementation of the wider time window, its effect on the admission-to-treatment time, and safety and functional outcome in patients recorded in SITS-ISTR. - Methods - Patients treated according to the criteria of the European Summary of Product Characteristics, except for the time window, were included. Patients were grouped according to whether they were registered into SITS-ISTR before or after October, 2008. We measured admission-to-treatment time and rates of symptomatic intracerebral haemorrhage, mortality, and functional independence at 3 months. - Findings - 23 942 patients were included in SITS-ISTR between December, 2002, and February, 2010, of whom 2376 were treated 3-4·5 h after symptom onset. The proportion of patients treated within 3-4·5 h by the end of 2009 was three times higher than in the first three quarters of 2008 (282 of 1293 [22%] vs 67 of 1023 [7%]). The median admission-to-treatment time was 65 min both for patients registered before and after October, 2008 (p=0·94). 352 (2%) of 21 204 patients treated within 3 h and 52 (2%) of 2317 treated within 3-4·5 h of stroke had symptomatic intracerebral haemorrhage at 3 months (adjusted odds ratio [OR] 1·44, 95% CI 1·05-1·97; p=0·02). 2287 (12%) of 18 583 patients who were treated within 3 h and 218 (12%) of 1817 who were treated within 3-4·5 h had died by the 3-month follow-up (adjusted OR 1·26, 95% CI 1·07-1·49; p=0·005); 10 531 (57%) of 18 317 patients treated within 3 h of stroke and 1075 (60%) of 1784 who were treated within 3-4·5 h were functionally independent at 3 months (adjusted OR 0·84, 95% CI 0·75-0·95; p=0·005). - Interpretation - Since October, 2008, thrombolysis within 3-4·5 h after stroke has been implemented rapidly, with a simultaneous increase in the number of patients treated within 3 h; admission-to-treatment time has not increased. Safety and functional outcomes are less favourable after 3 h, but the wider time window now offers an opportunity for treatment of those patients who cannot be treated earlier. Thrombolysis should be initiated within 4·5 h after onset of ischaemic stroke, although every effort should be made to treat patients as early as possible after symptom onset. - Funding - Boehringer Ingelheim, Ferrer, the European Union Public Health Executive Authority, and Medical Training and Research (ALF) from Stockholm County Council and Karolinska Institutet.
Gesehen am 12.03.2021